1985
DOI: 10.1002/jbm.820190806
|View full text |Cite
|
Sign up to set email alerts
|

Bioerodible polyanhydrides as drug‐carrier matrices. I: Characterization, degradation, and release characteristics

Abstract: Polyanhydrides based on a variety of aromatic and aliphatic dicarboxylic acids were developed as bioerodible carrier matrices for controlled delivery applications. The high hydrolytic reactivity of the anhydride linkage provides an intrinsic advantage over other classes of bioerodible polymers in versatility and control of degradation rates. For example, using the poly[bis(p-carboxyphenoxy) alkane anhydrides] as models, polymers with degradation rates in the range of 10(-1) to 10(-4) mg/h/cm2 were obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
243
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(251 citation statements)
references
References 19 publications
8
243
0
Order By: Relevance
“…To estimate the degradation rate constants for CPH in the copolymer, we compare the molar erosion rate constants for poly(CPH) to that for poly(SA) reported by Leong et al 51,52 The ratio of the erosion rate constants for poly(SA) to that for poly(CPH) is used as a first approximation for the ratio of degradation rate constants for the SA-SA and CPH-CPH bonds, k SA-SA and k CPH-CPH , respectively. We then estimate the degradation rate constant for CPH in the copolymer, k CPH , as…”
Section: Model Solution For Poly(cph:sa) 20:80mentioning
confidence: 99%
“…To estimate the degradation rate constants for CPH in the copolymer, we compare the molar erosion rate constants for poly(CPH) to that for poly(SA) reported by Leong et al 51,52 The ratio of the erosion rate constants for poly(SA) to that for poly(CPH) is used as a first approximation for the ratio of degradation rate constants for the SA-SA and CPH-CPH bonds, k SA-SA and k CPH-CPH , respectively. We then estimate the degradation rate constant for CPH in the copolymer, k CPH , as…”
Section: Model Solution For Poly(cph:sa) 20:80mentioning
confidence: 99%
“…Aliphatic polyanhydride homopolymers are often problematic materials as they are usually highly crystalline with unfavourable mechanical properties (Goepferich and Tessmar, 2002). Aromatic polyanhydrides erode slower than aliphatic ones (Leong et al, 1985), which is due to their increased hydrophobicity and the hindered approach of water to the anhydride bond (Tamada and Langer, 1992).…”
Section: Polyanhydridesmentioning
confidence: 99%
“…This is in contrast from what has been reported with the p(CPP:SA) polyanhydride. Leong et al [6] have reported that they could obtain a wide range of CPP erosion rates (1 week to several years) by increasing the monomer ratio of CPP to SA. However, Goepferich et al [7] have found that increasing CPP monomer content (although extending CPP release) does not actually affect SA release from p(CPP:SA).…”
Section: Time (Hours)mentioning
confidence: 99%
“…Differential Scanning Colorimetry (DSC) studies indicate that the polymer degree of crystallinity decreases with increasing FAD monomer content [4] (see Figure 4). Hydrophobicity inhibits water penetration into the polymer matrix, but amorphous domains are more vulnerable to hydrolytic attack [6,7], and therefore degrade more easily than crystalline regions. These two opposing copolymer properties may compromise the range of degradation rates that can be achieved by varying the monomer ratio in the p(FAD:SA) copolymer.…”
Section: Time (Hours)mentioning
confidence: 99%